Performance characteristics of mix oil biodiesel blends with smoke emissions - Sanjay Mohite; Sudhir Kumar; Sagar Maji (Center of Biomass & Renewable Energy, Diponegoro University, 2016)
Fossil fuel resources are being depleted day by day and its use affects the environment adversely. Renewable energy is one of the alternate for sustainable development and biodiesel is one of the suitable alternate which can replace the diesel. The major hurdles in the successful commercialization of biodiesel are high feedstock cost and conversion technology to reduce viscosity. The choice of raw material and biodiesel production method must depend upon techno-economical view. There are some specific regions for different types of oil availability. It is therefore required to produce biodiesel from the mixture of oils to fulfill the requirements of energy demand in a particular country according to its suitability and availability of feedstock. Karanja and Linseed crops are abundantly available in India. Biodiesel was produced from a mixture of Karanja and Linseed oils by alkaline transesterification. In this experimental study, biodiesel blends of 10%, 20% and 30% were used with diesel in a diesel engine at a constant speed of 1500 rpm with varying brake powers (loads) from 0.5 kW to 3.5kW to evaluate brake thermal efficiency, brake specific fuel consumption, brake specific energy consumption, exhaust gas temperature, mechanical efficiency, volumetric efficiency, air fuel ratio and smoke opacity. They were compared with diesel and found satisfactory. BTE was found to be 28.76% for B10 at 3.5kW load. Smoke opacity was also found to be reduced with all blends. Smoke opacity was found to be reduced up to 10.23% for B10 biodiesel blend as compared to that of diesel at 3.5kW. Experimental investigation has revealed that biodiesel produced from a mixture of Karanja and Linseed oils can be successfully used in diesel engines without any engine modification and B10 was found to be an optimum biodiesel blend in terms of brake thermal efficiency. Article History: Received April 14th 2016; Received in revised form June 25th 2016; Accepted July 10th 2016; Available onlineHow to Cite This Article: Mohite. S, Kumar, S. & Maji, S. (2016) Performance characteristics of mix oil biodiesel blends with smoke emissions. Int. Journal of Renewable Energy Development, 5(2), 163-170.http://dx.doi.org/10.14710/ijred.5.2.163-170